(NwERXTE MUZYKE (B/s - (NpLATEK(B, (NqKOW mOISEEWI^(B,s ((NmOSKWA (B:s (NsOWETSKIJ KOMPOZITOR(B,s, 1989)
(No WZAIMOSWQZQH MUZYKI I DRUGIH ISKUSSTWAH(B.s
(NpRIME^(B.: (NS(B. 341-350s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NmAQKOWSXKIJ w(B. (Nw(B.s; (NmANDELX[TAM o(B. (Ne(B.s; (NcWETA)QÃWA m(B. æ.s)E; (NpASTERNAK b(B. (Nl(B.s; (NaHMATOWA a(B. (Na(B.s; (NmUZIKAs -- (NwZA)QÃMOZW(B'(NQZKIs)E -- (NrOS)QÆQs)E -- 20 (NST(B.s; (NMUZIKAs; (NPOETIs; (NPISXMENNIKIs